STUDI HAMBATAN SERTIFIKASI KEAHLIAN TENAGA KERJA TERAMPIL KONSTRUKSI JALAN KOTA SUNGAI PENUH - Kastra, Fadil; Rita, Eva; Zulherman, Zulherman (SIGMA TEKNIKA, 2025)
The quality of good construction work is influenced by several factors, one of which is the workforce factor. Workers who have expertise and skills that meet standards greatly influence the quality of work. In order for workers to gain recognition for their abilities and competencies, competency certification is needed. However, in road construction work, there are still very few skilled workers who have competency certificates, especially those working on road construction work in Sungai Penuh City. This study aims to determine what obstacles and significant obstacles are faced by skilled workers in obtaining expertise certification. This study uses a qualitative method with descriptive statistical analysis. This study was conducted on road construction work in Sungai Penuh City with 30 respondents of skilled workers. The research design used was a survey and data collection through interviews, questionnaires, observations and literature studies. Obstacles in achieving skilled worker expertise certification in road construction work in Sungai Penuh City based on the results of interviews with workers are the lack of information regarding the importance of expertise certificates, limited certification institutions, quite high certification costs, difficult certification procedures, company concern for competence, no effect on wages. Significant obstacles in achieving certification of skilled labor expertise in road construction work in Sungai Penuh City based on ranking, namely the lack of information regarding the importance of expertise certificates 17.26%.